THE EFFECTIVENESS OF REGIONAL TAX REVENUE AT MINAHASA REGENCY IN 2020-2022 - Constantinopel Yuan Cakrawala Robot; Inggriani Elim; Priscilia Weku (Universitas Sam Ratulangi, 2023)
The purpose of this study is to determine the effectiveness of regional tax revenue at Minahasa Regency in 2020-2022. This research uses a quantitative descriptive research approach. The data used comes from the Regional Revenue Agency of Minahasa Regency, namely in the form of the 2020-2022 Regional Tax Target and Realization Report. The results of this study indicate that (1) The effectiveness of hotel tax revenue from 2020-2022 has increased, (2) The effectiveness of restaurant tax revenue from 2020-2022 has increased, (3) The effectiveness of entertainment tax revenue from 2020-2022 is consistently very effective, (4) The effectiveness of advertisement tax revenue from 2020-2022 has decreased, (5) The effectiveness of street lighting tax revenue from 2020-2022 is consistently very effective, (6) The effectiveness of parking tax revenue from 2020-2022 has increased, (7) The effectiveness of groundwater tax revenues from 2020-2022 has decreased, (8) The effectiveness of swallow's nest tax revenue from 2020-2022 has increased, (9) The effectiveness of MBLB's tax revenues from 2020-2022 has increased, (10) The effectiveness of PBB-P2 revenues from 2020-2022 is consistently very effective, (11) The effectiveness of BPHTB revenues from 2020-2022 has fluctuated.